Charge Transfer: Identifying Ionic and Electronic Charge Transfer at Oxide Heterointerfaces (Adv. Mater. 4/2021). Issue 4 (25th January 2021) - Rose, Marc‐André; Šmíd, Břetislav; Vorokhta, Mykhailo; Slipukhina, Ivetta; Andrä, Michael; Bluhm, Hendrik; Duchoň, Tomáš; Ležaić, Marjana; Chambers, Scott A.; Dittmann, Regina; Mueller, David N.; Gunkel, Felix
Abstract : In article number 2004132, Marc‐André Rose, David N. Mueller, Felix Gunkel, and co‐workers identify how ion and electron transfer naturally balance at the LaAlO3 /SrTiO3 oxide heterointerface, affecting the band alignment and magnetic signature of the interface. They utilize near‐ambient‐pressure X‐ray photoelectron spectroscopy, showing that Sr ions are more mobile at the interface than in the bulk, and implicating a high importance of ionic charge transfer in oxide heterostructures.